Manufacturers' tailored responses to powerful supply chain partners. Issue 3 (28th May 2021) - Tao, Zhexiong; Li, Shanling; Ray, Saibal; Rebolledo, Claudia
Abstract : Purpose: This study aims to investigate how relatively weaker manufacturers respond to the dominance of stronger suppliers and/or customers. The study also analyzes how the competitive intensity perceived by manufacturers moderates their responses to powerful chain partners. Design/methodology/approach: Using hierarchical regression, data from 1, 417 manufacturing companies sampled from the fifth and sixth versions of the International Manufacturing Strategy Survey were analyzed. Findings: This study found that relatively weaker manufacturers often adopt exploration strategies to countervail the dominance of suppliers and adopt exploitation strategies to deal with more powerful customers. In dealing with both dominant suppliers and customers, relatively weaker manufacturers are prone to adopt exploration and exploitation strategies simultaneously and hence become ambidextrous. Furthermore, the link between dominance in supply chains and the exploration (exploitation) strategy is strengthened (weakened) as market competition perceived by manufacturers intensifies. Originality/value: The contribution of this paper is multi-folds. First, this paper develops and test a novel theoretical model on how relatively weaker manufacturers create tailored strategies to defend their positions in the supply chain. Second, it integrates resource dependence theory and organizational learning theory to propose that relatively weaker manufacturers could use a unique configuration of exploration and exploitation strategies to counteract the dominance of their suppliers and customers. Third, it investigates supply chain power by considering the manufacturers' upstream and downstream powerful partners together, rather than individually and fourth, it reveals that relationships linking supply chain power to manufacturers' tailored strategies are contingent on competitive intensity.